Analisis Preferensi Anak Usia Dini terhadap Tabungan Pintar dalam Mengembangkan Literasi Keuangan di TK-IT Wildani 6 Desa Menongo Kec. Sukodadi Kab. Lamongan - Arlika, Fivin Aulia (AJER: Advanced Journal of Education and Religion, 2025)
The low interest and engagement of early childhood children in saving activities impact their limited understanding of financial literacy concepts. Therefore, an educational medium that is appropriate for the children’s developmental stage is needed. This research aims to analyze the use of a smart savings tool (tabungan pintar) in developing the financial literacy of early childhood children at TK-IT Wildani 6 Menongo, Sukodadi District, Lamongan Regency. The study employed a descriptive qualitative approach with a total of 27 children from Group B serving as the subjects. Data were collected through observation, interviews, and documentation, and subsequently analyzed using data reduction, data display, and conclusion drawing. The results indicate that the smart savings tool holds significant meaning for the children as it facilitates their understanding of the concept of money and the practice of saving in a straightforward manner. This medium also made a tangible contribution to the development of financial literacy, evidenced by an increase in the children’s understanding of monetary value, motivation, and discipline. Furthermore, the children demonstrated a positive preference for using the smart savings tool through active engagement with its simple digital features. Thus, the smart savings tool is proven to be effective as an educational medium for strengthening early childhood financial literacy while simultaneously fostering an interest in saving from an early age.